Integrated Pretreatment Optimization of PVA-Sized Lightweight Cotton Fabric Using Multifunctional Auxiliaries and Alkaline–Peroxide Systems - Ratih Kurniasari; Mona Maulatul Fitriah (Practice of Fashion and Textile Education Journal, 2026)
Cotton fabric preparation, comprising desizing, scouring, and bleaching, critically determines fabric quality prior to dyeing and finishing. This study investigated the effects of preparation process sequencing and multifunctional auxiliary concentration (Clarite One) on the physical properties of lightweight cotton fabric, including tear strength, absorbency, and whiteness index. C41166 cotton fabric was processed using three preparation methods: three-step, two-step, and one-step (simultaneous) systems, combined with Clarite One concentrations of 4, 8, and 10 g/L. Physical properties were evaluated according to SNI ISO 13937-1 (tear strength), AATCC 197 (absorbency), and AATCC 110 (whiteness). Data were analyzed using two-factor ANOVA followed by the Newman–Keuls post hoc test at a 95% confidence level. The results demonstrated that both process sequencing and auxiliary concentration significantly affected fabric performance. The optimum condition was achieved using the one-step method with 4 g/L Clarite One, producing the highest tear strength, adequate absorbency, and whiteness meeting commercial standards. Furthermore, the one-step process improved operational efficiency by reducing processing time and chemical consumption, highlighting its potential for enhancing productivity and sustainability in industrial cotton pretreatment